2018
DOI: 10.1111/acps.12989
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine and all‐cause mortality in treatment‐resistant schizophrenia: a historical cohort study

Abstract: Objective Large‐scale epidemiological studies have demonstrated a protective effect of clozapine on mortality in people with schizophrenia. Clozapine is reserved for use in patients with treatment‐resistant schizophrenia (TRS), but evidence of clozapine's effect on mortality exclusively within TRS samples is inconclusive. Hence, we aimed to investigate the effect of clozapine use on all‐cause mortality in TRS patients. Methods A historical patient cohort sample of 2837 patients, who met criteria for TRS betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 43 publications
3
58
0
Order By: Relevance
“…Although CLZ can interact with genetic factors to evoke rare but potentially fatal complications such as agranulocytosis and neutropenia 42 , CLZ is currently one of the most commonly used atypical antipsychotic drugs for treatment-resistant schizophrenia 10 . As CLZ readily crosses the blood-brain barrier, it can be used reliably to activate DREADD receptors in a variety of chemogenetic experiments, replacing CNO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CLZ can interact with genetic factors to evoke rare but potentially fatal complications such as agranulocytosis and neutropenia 42 , CLZ is currently one of the most commonly used atypical antipsychotic drugs for treatment-resistant schizophrenia 10 . As CLZ readily crosses the blood-brain barrier, it can be used reliably to activate DREADD receptors in a variety of chemogenetic experiments, replacing CNO.…”
Section: Discussionmentioning
confidence: 99%
“…CLZ is an atypical antipsychotic drug, most commonly used in patients with treatment-resistant schizophrenia 10 . CLZ has been suggested for use in chemogenetic neuromodulation, in place of CNO, because it readily crosses the blood-brain barrier 4,7 .…”
mentioning
confidence: 99%
“…Regarding clozapine, in a meta-analysis of 24 studies with long-term follow-up of treatment, Vermeulen et al [114] found long-term, crude mortality rate ratios were significantly lower in patients continuously treated with clozapine compared to patients treated with other antipsychotics (mortality rate ratio = 0.56). Online supplementary Box S4 [112][113][114][115][116] describes two additional studies published after the meta-analysis, also showing lower mortality in clozapine patients [115,116]…”
Section: Baseline Risk Of Poor Outcomes From Trs Without Treatmentmentioning
confidence: 99%
“…Tertiary care programs for TRS should include individually tailored psychosocial rehabilitation, as well as personalised and evidence-based medication management, to achieve flexible and effective care. 9 Clozapine is the only recommended antipsychotic treatment for TRS and is the most effective agent for reducing symptoms, 10 hospital use, 11 suicide rates, 12,13 aggressive behaviour, 14 violent crime 15 and substance misuse. 16 However, the management of clozapine therapy for patients with severe and chronic behavioural problems requires carefully developed strategies and close monitoring of adverse effects, which can be challenging in a primary or secondary care setting.…”
Section: Tertiary Services For Complex Trsmentioning
confidence: 99%